Effect of Potassium Salt Addition on Silver Precipitation During Hydrothermal Synthesis of Argentojarosites - Olga Cheremisina; Roman Vasiliev; Aleksei Fedorov (Metals)
This paper presents the laboratory study results of the hydrothermal synthesis of compounds structurally related to the jarosite group, which is characterized by basic iron sulfate AFe3(SO4)2(OH)6 as the main structural component containing A+ cations such as K+, Ag+, and NH4+. The synthesis process involves preparing the initial model solution using soluble salts of the studied metals, either jointly or individually. The resulting solution is then processed in a sealed vessel (autoclave) at a temperature exceeding 100 °C. This study was conducted within a temperature range of 105–200 °C, with experiment durations varying and a maximum dwell time of 300 min. The zero-time value was defined as the moment the autoclave reached the required temperature. It was observed that adding potassium salts to the solution during hydrothermal synthesis reduced the amount of silver precipitated as argentojarosite. An increase in process temperature from 105 °C to 200 °C resulted in a rise in silver precipitation, from 35% to 69%. The equilibrium constants of the reactions involved in the precipitation of specific jarosite group compounds were calculated, and the reaction order was determined.